Plating structure having Ni electroplating film and lead frame including the same
By adding an appropriate amount of phosphorus to the Ni electroplating film, an excellent Ni electroplating film is solved, and the cost of thinning and welding performance is reduced.
Patent Information
- Application Number
- CN202180065149.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-28
- Filing Date
- 2021-12-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-12-21
AI Technical Summary
In the prior art, the solder wetting properties of the Ni coating film are insufficient, resulting in an increase in cost during the film-thinning process and it is difficult to maintain good solder wetting properties.
By adding a predetermined amount of P(phosphorus) to the Ni electroplating film, the phosphorus-containing Ni electroplating film is formed, and the structure and thickness of the coating are optimized to improve solder wettability.
It is achieved to shorten the filmization time of Ni coating while maintaining good solder wetting properties, reduce costs, and ensure excellent performance of coating.
Smart Images

Figure BDA0004140805480000101 
Figure BDA0004140805480000111 
Figure BDA0004140805480000121
Abstract
Description
Technical Field
[0001] The present invention relates to a Ni electroplated film and a plated structure having the plated film, and in particular to a plated structure in a bonding portion such as a wire bond in a semiconductor package such as an IC or LSI. Background Art
[0002] As a method for mounting a semiconductor element on a substrate in a semiconductor package such as an IC or LSI, a flip chip method using a protruding terminal called a bump for electrical connection and a method using a lead frame for electrical connection to an external wiring (wire bonding) are known. Regarding flip chip mounting, for example, Patent Documents 1 to 4 disclose forming an electroless plating film of Ni / Pd / Au on a connection terminal portion of a semiconductor element and forming a solder bump thereon.
[0003] On the other hand, regarding wire bonding, the present applicant has previously provided an invention regarding a plating structure consisting of three layers of Ge-Ni / Pd / Au formed by electroplating (Patent Document 5). In addition, a technique for forming a Ni / Pd-P / Au coating by electroplating is also known (Patent Document 6). The above-mentioned coating can be formed by electroplating or electroless plating, but electroplating and electroless plating each have advantages and disadvantages, and therefore are generally used separately according to the object to be plated.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 11-345896
[0007] Patent Document 2: Japanese Patent Application Publication No. 2006-179797
[0008] Patent Document 3: International Publication No. 2006 / 112215
[0009] Patent Document 4: Japanese Patent Application Publication No. 2016-162770
[0010] Patent Document 5: Japanese Patent Application Publication No. 2009-228021
[0011] Patent Document 6: Japanese Patent Application Publication No. 2012-241260 Summary of the invention
[0012] Problems to be solved by the invention
[0013] As one of the surface treatment methods for lead frames, there is a method called Pd-PPF (Pre Plated Frame) (see Patent Document 6). This is a method of applying Ni / Pd / Au three-layer plating to the entire surface of a Cu-based lead frame, thereby improving solder wettability and achieving sufficient bonding performance. As an attempt to reduce the cost of this Pd-PPF lead frame, the thinning of precious metal coatings such as Au and Pd has been promoted.
[0014] Thinning of the precious metal plating film must not impair solder wettability. Whether this effect can be maintained is determined by evaluating the solder wettability of the plating film after heat treatment. For example, as described in Patent Document 5, a test piece with a plating film is heated and then immersed in a solder bath, and the time until the wetting stress value reaches zero (zero crossing time: ZCT) is measured. If this time is short enough, it can be considered that solder wettability is maintained.
[0015] In the prior art, Au and Pd platings have become able to maintain sufficient solder wettability even at a thickness of several nm to tens of nm, and the cost reduction brought about by the thin filming of precious metal platings has reached its limit. On the other hand, there is still room for improvement in Ni platings. By improving the characteristics of Ni platings (solder wettability), thin films can be made, and it is expected that costs can be further reduced by shortening the cycle time. The present invention was completed in view of such problems, and its purpose is to take the following as the subject: to provide a Ni plating with excellent solder wettability and a plated structure having the Ni plating.
[0016] Means for solving problems
[0017] The present inventors have conducted intensive research to solve the above problems and have found that a Ni (nickel) plating film containing a predetermined amount of P (phosphorus) can form a Ni plating film with excellent solder wettability, thereby completing the present invention. The above problems are solved by the following means.
[0018] 1) A plating structure, comprising: a substrate composed of Cu or a Cu alloy, a Ni electroplating film formed on the substrate, a Pd electroplating film formed on the Ni electroplating film, and an Au electroplating film formed on the Pd electroplating film, wherein:
[0019] The Ni electroplating film contains 0.01 wt % or more and 1.0 wt % or less of P,
[0020] When the P content is 0.01 wt % or more and less than 0.05 wt %, the film thickness of the Ni electroplating film is 0.1 μm or more and 10 μm or less.
[0021] When the P content is 0.05 wt % or more and less than 0.2 wt %, the film thickness of the Ni electroplating film is 0.06 μm or more and 10 μm or less.
[0022] When the P content is 0.2 wt % or more and 1.0 wt % or less, the film thickness of the Ni electroplating film is 0.01 μm or more and 10 μm or less.
[0023] 2) A plated structure, comprising: a substrate composed of Cu or a Cu alloy, a Ni electroplated film formed on the substrate, and a Pd electroplated film formed on the Ni electroplated film, wherein:
[0024] The Ni electroplating film contains 0.01 wt % or more and 1.0 wt % or less of P,
[0025] When the content of P is 0.01 wt % or more and less than 0.05 wt %, the thickness of the Ni electroplating film is 0.1 μm or more and 10 μm or less.
[0026] When the content of P is 0.05 wt % or more and less than 0.2 wt %, the thickness of the Ni electroplated film is 0.06 μm or more and 10 μm or less.
[0027] When the content of P is 0.2 wt % or more and 1.0 wt % or less, the film thickness of the Ni electroplating film is 0.01 μm or more and 10 μm or less.
[0028] 3) A plated structure, comprising: a substrate composed of Cu or a Cu alloy, a Ni electroplated film formed on the substrate, and an Au electroplated film formed on the Ni electroplated film, wherein:
[0029] The Ni electroplating film contains 0.01 wt % or more and 1.0 wt % or less of P,
[0030] When the content of P is 0.01 wt % or more and less than 0.05 wt %, the thickness of the Ni electroplating film is 0.1 μm or more and 10 μm or less.
[0031] When the content of P is 0.05 wt % or more and less than 0.2 wt %, the thickness of the Ni electroplated film is 0.06 μm or more and 10 μm or less.
[0032] When the content of P is 0.2 wt % or more and 1.0 wt % or less, the film thickness of the Ni electroplating film is 0.01 μm or more and 10 μm or less.
[0033] 4) The plated structure according to any one of 1) to 3) above, wherein a metal strike plated film containing any one of Au, Ag, Pd and Cu is formed as a base of the Ni plated film.
[0034] 5) The plated structure according to any one of 1) to 4) above, wherein a metal strike plated film containing any one of Au, Ag and Pd is formed as a base of the Pd plated film and / or the Au plated film.
[0035] 6) A lead frame comprising the plating structure according to any one of 1) to 5) above.
[0036] Effects of the Invention
[0037] According to the present invention, it is possible to obtain a Ni electroplated film having excellent solder wettability. In addition, it is possible to achieve a thin film of the Ni electroplated film while maintaining good solder wettability. In the film forming process of the plated film, the Ni plated film takes a particularly long time to form, so by thinning the Ni plated film, the cycle time can be greatly shortened. DETAILED DESCRIPTION
[0038] Electroless plating does not use electricity and is not affected by current, so it can be plated uniformly. On the other hand, since it uses chemical reaction to form a coating, the coating formation speed is slow. In addition, the plating bath needs to be chemically stable, and the maintenance of the chemical solution and plating tank sometimes costs money. Based on such a situation, when forming a plating film on the entire surface of the lead frame, the plating film is usually formed by electroplating.
[0039] The inventors have conducted in-depth research on improving the solder wettability of such a plated film, and found that the solder wettability of the plated film can be improved by making the Ni plated film contain a predetermined amount of P (phosphorus). In particular, it was found that even when the Ni plated film is made thinner, sufficient solder wettability can be maintained. As a result, it is expected that the cycle time caused by the thinning of the Ni plated film can be shortened and the cost can be reduced.
[0040] The Ni electroplated film according to an embodiment of the present invention is characterized in that it contains P (phosphorus) in an amount of 0.01% by weight or more and 1.0% by weight or less. By making the phosphorus content in the Ni plating film within the above range, the solder wettability of the Ni plating film can be improved. On the other hand, when the P content is less than 0.01% by weight, the effect of improving solder wettability cannot be obtained. In addition, when the P content is greater than 1.0% by weight, the solder wettability is reduced. The lower limit of the P content is preferably 0.08% by weight or more, more preferably 0.18% by weight or more, and the upper limit of the P content is preferably 0.8% by weight or less, more preferably 0.61% by weight or less.
[0041] When a Ni electroplated film containing P (phosphorus) was observed using a scanning electron microscope, it was found that as the phosphorus content increased, the particles of the Ni electroplated film tended to be miniaturized. In addition, the following was found: when the Ni electroplated film was heated, the crystals expanded compared to before heating, but the higher the P content, the more the crystal expansion was suppressed. It is believed that such crystal miniaturization is due to the concentration of phosphorus at the grain boundaries, which hinders crystal growth. It is believed that the reason for the reduction in solder wettability is that the base metal (Cu or Cu alloy, etc.) diffuses to the outermost surface of the plating film and is exposed to the atmosphere and oxidized, but it is believed that such phosphorus concentrated at the grain boundaries inhibits the diffusion of the base metal, thereby inhibiting the reduction in solder wettability.
[0042] The film thickness of the Ni electroplating film can be determined by the relationship with the content of P. When the content of P is 0.01 wt% or more and less than 0.05 wt%, the film thickness of the Ni electroplating film is 0.1 μm or more and 10 μm or less. When the content of P is 0.05 wt% or more and less than 0.2 wt%, the film thickness of the Ni electroplating film is 0.06 μm or more and 10 μm or less. When the content of P is 0.2 wt% or more and 1.0 wt% or less (or 0.8 wt% or less, 0.61 wt% or less), the film thickness of the Ni electroplating film is set to 0.01 μm or more and 10 μm or less. The Ni electroplating film of this embodiment can ensure good solder wettability even when the film thickness of the Ni electroplating film is reduced to less than 1 μm, which can be said to be particularly excellent in this regard.
[0043] When the P content is 0.01 wt % or more and less than 0.05 wt %, if the Ni plating film is thinner than 0.1 μm, the diffusion prevention effect of the base metal (Cu or Cu alloy) is weakened, Cu oxide is formed on the surface, and solder wettability is reduced.
[0044] In addition, when the P content is greater than 0.05 wt% and less than 0.2 wt%, if the Ni plating film is thinner than 0.06 μm, the diffusion prevention effect of the base metal (Cu or Cu alloy) becomes weak, Cu oxide is formed on the surface, and solder wettability is reduced.
[0045] In addition, when the content of P is 0.2 wt% or more and 1.0 wt% or less, if the film thickness of the Ni plating film is thinner than 0.01 μm, the diffusion prevention function of the base metal (Cu or Cu alloy) is weakened and the solder wettability is reduced as described above. The film thickness is preferably 0.06 μm or more, more preferably 0.1 μm or more, and further preferably 0.2 μm or more.
[0046] It should be noted that the thicker the Ni electroplating film is, the higher the solder wettability is. However, when the film thickness is thicker than necessary, there is excess Ni adhesion, which increases the cost. Therefore, the film thickness is set to 10 μm or less, more preferably 5 μm or less, further preferably 1 μm or less, and most preferably 0.5 μm or less.
[0047] The plating structure according to the embodiment of the present invention can have the following structures.
[0048] Structure (I):
[0049] (Substrate) / Ni coating / Pd coating / Au coating (outermost surface)
[0050] Structure (II):
[0051] (Substrate) / Ni coating / Pd coating (outermost surface)
[0052] Structure (III):
[0053] (Substrate) / Ni coating / Au coating (outermost surface)
[0054] Here, the Ni plating film is a P-containing Ni electroplating film according to the present embodiment.
[0055] Any of the above-mentioned coatings can be formed by electroplating. The Pd coating can be not only pure Pd, but also a Pd alloy. When Cu or a Cu alloy is used as a substrate (base metal), this embodiment is particularly effective, but does not prevent the use of other materials, such as Fe, Fe alloys. The above-mentioned plated structure can be selected according to the application and the required characteristics. The main purpose of the Au coating and Pd coating formed on the outermost surface is to prevent the oxidation of the Ni coating and prevent Ni from diffusing to the surface.
[0056] A metal impact plating film can be formed as a base under each of the Ni plating film, the Pd plating film, and the Au plating film. Generally speaking, impact plating is sometimes performed as a pretreatment for the purpose of improving the adhesion of the electroplated film. In the case of forming a Ni plating film, it is preferred to perform metal impact plating containing any one of Au, Ag, Pd, and Cu. In the case of forming a Pd plating film and / or an Au plating film, it is preferred to perform metal impact plating containing any one of Au, Ag, and Pd. There is no particular restriction on the film thickness of the metal impact plating film, for example, it can be set to 0.001μm to 0.5μm. Preferably, it is 0.01μm to 0.1μm.
[0057] Another embodiment of the present invention is a lead frame having the above-mentioned plating structure. The lead frame is mostly made of copper or copper alloy. By forming the plating structure involved in this embodiment on such a lead frame, excellent bonding can be achieved in lead bonding and welding. It should be noted that the plating structure involved in this embodiment can be formed not only on the lead frame, but also on the solder bump pad part used in flip chip mounting, and it can be inferred that excellent bonding can also be achieved.
[0058] In addition, depending on the different objects to be plated, a Ni / Pd / Au coating is sometimes formed by electroless plating. In the case of electroless plating, a phosphorus compound is sometimes used as a reducing agent in the plating solution. In this case, P (phosphorus) must be contained in the Ni coating. By using a reducing agent other than a phosphorus compound, a Ni coating with a P content of 0 wt% can also be formed, but since it comes from the reducing agent, it is very difficult to control the P content in the Ni coating to less than 2 wt%.
[0059] The Ni plating film involved in this embodiment can be formed by electroplating using a nickel plating bath containing a phosphorus compound. As the phosphorus compound, hypophosphorous acid, phosphorous acid, phosphoric acid, etc. can be used. In addition, other phosphorus-containing compounds can be used instead. The nickel plating bath can use a Watt bath, a sulfonamide bath, a citric acid bath, etc. In addition, other nickel-containing plating baths can be used instead. The phosphorus compound and nickel plating bath shown above are illustrative and not limiting.
[0060] The amount of nickel salt in the Ni plating bath can be set to 40 g / L to 125 g / L in terms of metal. In addition, the amount of phosphorus compound can be set to 5 mg / L to 300 mg / L in terms of phosphorus. The amounts of nickel salt and phosphorus compound shown above are illustrative and should not be construed as intended to be limited to the disclosed range.
[0061] The Ni electroplating conditions may be as follows. However, the electroplating conditions are exemplary, and it is apparent that there are a variety of processing systems and processing devices for implementing Ni electroplating, and the electroplating conditions may also be changed according to the processing systems and processing devices. Therefore, it should be noted that the electroplating conditions disclosed are not intended to be limited thereto.
[0062] Cathode current density: 1A / dm 2 ~10A / dm 2
[0063] Electrolysis time: 5 minutes to 30 minutes
[0064] pH: 3-6
[0065] Bath temperature: 30℃~60℃
[0066] Cathode: Copper or copper alloy
[0067] Anode: Nickel
[0068] The Pd plating film and the Au plating film can be formed using a known plating bath and known electroplating conditions (for example, Patent Document 5). In addition, the metal strike plating film can also be formed using a known plating bath and known electroplating conditions.
[0069] [Example]
[0070] Next, examples and comparative examples of the present invention will be described. It should be noted that the following examples are only representative examples, and the present invention is not necessarily limited to these examples, but should be interpreted within the scope of the technical concept described in the specification.
[0071] <About the preparation of evaluation samples>
[0072] Electrolytic degreasing of lead frames made of Cu alloy (liquid temperature: 68°C, current density: 10A / dm 2 , immersion time: 60 seconds) as pretreatment, followed by pickling (5 volume % sulfuric acid, 30 seconds), and then washing with pure water. Under the following plating conditions, Ni plating, Pd plating, and Au plating were performed on the pretreated lead frame in sequence. At this time, the P concentration in the Ni plating solution was changed to adjust the evaluation sample.
[0073] (Ni plating conditions)
[0074] Bath: Matt Watt bath containing phosphorus compounds
[0075] Ni concentration: 66g / L
[0076] P concentration: 0mg / L~200mg / L
[0077] Current density: 5A / dm 2
[0078] Bath temperature: 50°C
[0079] pH: 4
[0080] Target film thickness: 0.13μm
[0081] (Pd plating conditions)
[0082] Plating bath: Palladium plating solution (manufactured by Matsuda Industry Co., Ltd.: Palla Sigma UF)
[0083] Pd concentration: 3g / L
[0084] Current density: 0.5A / dm 2
[0085] Bath temperature: 40°C
[0086] pH: 6.5
[0087] Target film thickness: 0.025μm
[0088] Anode: Iridium oxide
[0089] (Au plating conditions)
[0090] Plating bath: Gold plating solution (manufactured by Matsuda Industry Co., Ltd.: Auru Sigma F)
[0091] Au concentration: 2g / L
[0092] Current density: 2A / dm 2
[0093] Bath temperature: 45°C
[0094] pH: 4
[0095] Target film thickness: 0.005μm
[0096] Anode: Iridium oxide
[0097] (Determination of phosphorus content)
[0098] The phosphorus content in the Ni plating film of each evaluation sample can be measured using a high-frequency inductively coupled plasma (ICP) emission spectrometer.
[0099] (Evaluation of solder wettability)
[0100] The solder wettability was evaluated by keeping each evaluation sample under a predetermined temperature condition (400°C ± 2°C) for a certain period of time, applying a high temperature thermal history, and then immersing it in a solder bath (63%-Sn, 37%-Pb, liquid temperature: 230°C ± 5°C). The time required for the force received from the solder bath to become zero (zero crossing time) was measured. The shorter the zero crossing time, the better the solder wettability. For the immersion conditions in the solder bath, the immersion depth was set to 1 mm, the immersion speed was set to 2 mm / second, the immersion time was set to 5 seconds, and R-type flux (inactive type) was used as a soldering accelerator.
[0101] <Evaluation of P content in Ni plating film>
[0102] The relationship between the P content contained in the Ni coating and the zero crossing time is shown in Table 1. As shown in Table 1, by adding phosphorus, it is confirmed that the solder wettability is improved. In particular, when the phosphorus content is 0.1 wt % or more and 0.8 wt % or less, the solder wettability is greatly improved. It should be noted that, generally, the solder wettability of the Pb-free solder is worse than that of the Pb-Sn solder, but it is confirmed that there is no problem with the solder wettability even when the Pb-free solder (Sn-3.0Ag-0.5Cu) is used.
[0103] [Table 1]
[0104]
[0105] <Evaluation of Thin-film Formation of Ni Plating>
[0106] The P concentration in the Ni plating solution was set to 5.4 mg / L, 10.9 mg / L, 32.7 mg / L, 76.3 mg / L, and 119.9 mg / L, and the Ni plating thickness was changed as shown in Table 2. In addition, the evaluation samples were made under the same plating conditions as above. Then, the solder wettability of various samples was evaluated under the same conditions as above. It should be noted that for the plating thickness of 0.13 μm, the results of Table 1 were directly quoted. The results are shown in Table 2. As shown in Table 2, even if the film thickness of the Ni plating is less than 1.0 μm, it can be confirmed that good solder wettability can be maintained. It should be noted that the thicker the film thickness of the Ni plating, the higher the solder wettability. Therefore, for a film thickness greater than 0.3 μm, although not shown in the examples, it was confirmed that there was no problem with solder wettability.
[0107] [Table 2]
[0108]
[0109] <Formation of Metal Impact Plating>
[0110] Electrolytic degreasing of lead frames made of Cu alloy (liquid temperature: 68°C, current density: 10A / dm 2 , immersion time: 60 seconds) as pretreatment, followed by pickling (5 volume % sulfuric acid, 30 seconds), and then washing with pure water. The pretreated lead frame is subjected to Cu impact plating, Ni plating, Pd plating, and Au plating in sequence. At this time, the P concentration in the Ni plating solution is changed to adjust the evaluation sample. It should be noted that Ni plating, Pd plating, and Au plating are carried out under the same conditions as above, and the impact plating is as follows.
[0111] (Cu impact plating conditions)
[0112] Plating bath: Cu impact plating solution
[0113] Cu concentration: 40g / L
[0114] Current density: 1A / dm 2
[0115] Bath temperature: 25°C
[0116] pH: 13
[0117] Target film thickness: 0.001μm
[0118] Anode: Iridium oxide
[0119] <Evaluation of Thin-film Formation of Ni Plating>
[0120] The relationship between the P content contained in the Ni coating and the zero crossing time is shown in Table 3. As shown in Table 3, it is confirmed that the solder wettability is improved by adding phosphorus. In particular, when the phosphorus content is 0.1 wt % or more and 0.8 wt % or less, the solder wettability is greatly improved. It should be noted that, generally, the solder wettability of the Pb-free solder is worse than that of the Pb-Sn solder, but it is confirmed that there is no problem with the solder wettability even when the Pb-free solder (Sn-3.0Ag-0.5Cu) is used.
[0121] [Table 3]
[0122]
[0123] <Evaluation of Thin-film Formation of Ni Plating>
[0124] The P concentration in the Ni plating solution was set to 5.4 mg / L, 10.9 mg / L, 32.7 mg / L, 76.3 mg / L, and 119.9 mg / L, and the Ni plating thickness was changed as shown in Table 4. In addition, the evaluation samples were made under the same plating conditions as above. Then, the solder wettability of various samples was evaluated under the same conditions as above. It should be noted that for a plating thickness of 0.13 μm, the results of Table 3 are directly cited. The results are shown in Table 4. As shown in Table 4, even if the film thickness of the Ni plating is less than 1.0 μm, it can be confirmed that good solder wettability can be maintained. It should be noted that the thicker the film thickness of the Ni plating, the higher the solder wettability. Therefore, for a film thickness greater than 0.3 μm, although not shown in the examples, it was confirmed that there was no problem with solder wettability.
[0125] [Table 4]
[0126]
[0127] <Formation of Metal Impact Plating>
[0128] Electrolytic degreasing of lead frames made of Cu alloy (liquid temperature: 68°C, current density: 10A / dm 2 , immersion time: 60 seconds) as pretreatment, followed by pickling (5 volume % sulfuric acid, 30 seconds), and then washing with pure water. The pretreated lead frame is subjected to Ni plating, Pd impact plating, Pd plating, and Au plating in sequence. At this time, the P concentration in the Ni plating solution is changed to adjust the evaluation sample. It should be noted that Ni plating, Pd plating, and Au plating are carried out under the same conditions as above, and impact plating is as follows.
[0129] (Pd impact plating conditions)
[0130] Plating bath: Pd impact plating solution
[0131] Pd concentration: 1.5g / L
[0132] Current density: 1.5A / dm 2
[0133] Bath temperature: 50°C
[0134] pH: 9
[0135] Target film thickness: 0.001μm
[0136] Anode: Iridium oxide
[0137] <Evaluation of Thin-film Formation of Ni Plating>
[0138] The relationship between the P content contained in the Ni coating and the zero crossing time is shown in Table 5. As shown in Table 5, it is confirmed that the solder wettability is improved by adding phosphorus. In particular, when the phosphorus content is 0.1 wt% or more and 0.8 wt% or less, the solder wettability is greatly improved. It should be noted that, generally, the solder wettability of the Pb-free solder is worse than that of the Pb-Sn solder, but it is confirmed that there is no problem with the solder wettability even when the Pb-free solder (Sn-3.0Ag-0.5Cu) is used.
[0139] [Table 5]
[0140]
[0141] <Evaluation of Thin-film Formation of Ni Plating>
[0142] The P concentration in the Ni plating solution was set to 5.4 mg / L, 10.9 mg / L, 32.7 mg / L, 76.3 mg / L, and 119.9 mg / L, and the Ni plating thickness was changed as shown in Table 6. In addition, the evaluation samples were made under the same plating conditions as above. Then, the solder wettability of various samples was evaluated under the same conditions as above. It should be noted that for the plating thickness of 0.13 μm, the results of Table 5 were directly quoted. The results are shown in Table 6. As shown in Table 6, even if the film thickness of the Ni plating is less than 1.0 μm, it can be confirmed that good solder wettability can be maintained. It should be noted that the thicker the film thickness of the Ni plating, the higher the solder wettability. Therefore, for a film thickness greater than 0.3 μm, although not shown in the examples, it was confirmed that there was no problem with solder wettability.
[0143] [Table 6]
[0144]
[0145] <Formation of Metal Impact Plating>
[0146] Electrolytic degreasing of lead frames made of Cu alloy (liquid temperature: 68°C, current density: 10A / dm 2 , immersion time: 60 seconds) as pretreatment, followed by pickling (5 volume % sulfuric acid, 30 seconds), and then washing with pure water. The pretreated lead frame is subjected to Ni plating, Pd plating, Au impact plating, and Au plating in sequence. At this time, the P concentration in the Ni plating solution is changed to adjust the evaluation sample. It should be noted that Ni plating, Pd plating, and Au plating are carried out under the same conditions as above, and impact plating is as follows.
[0147] (Au impact plating conditions)
[0148] Plating bath: Au impact plating solution
[0149] Au concentration: 1.0g / L
[0150] Current density: 5A / dm 2
[0151] Bath temperature: 50°C
[0152] pH: 4
[0153] Target film thickness: 0.001μm
[0154] Anode: Iridium oxide
[0155] <Evaluation of Thin-film Formation of Ni Plating>
[0156] The relationship between the P content contained in the Ni coating and the zero crossing time is shown in Table 7. As shown in Table 7, it is confirmed that the solder wettability is improved by adding phosphorus. In particular, when the phosphorus content is 0.1 wt% or more and 0.8 wt% or less, the solder wettability is greatly improved. It should be noted that, generally, the solder wettability of the Pb-free solder is worse than that of the Pb-Sn solder, but it is confirmed that there is no problem with the solder wettability even when the Pb-free solder (Sn-3.0Ag-0.5Cu) is used.
[0157] [Table 7]
[0158]
[0159] <Evaluation of Thin-film Formation of Ni Plating>
[0160] The P concentration in the Ni plating solution was set to 5.4 mg / L, 10.9 mg / L, 32.7 mg / L, 76.3 mg / L, and 119.9 mg / L, and the Ni plating thickness was changed as shown in Table 8. In addition, the evaluation samples were made under the same plating conditions as above. Then, the solder wettability of various samples was evaluated under the same conditions as above. It should be noted that for the plating thickness of 0.13 μm, the results of Table 7 were directly quoted. The results are shown in Table 8. As shown in Table 8, even if the film thickness of the Ni plating is less than 1.0 μm, it can be confirmed that good solder wettability can be maintained. It should be noted that the thicker the film thickness of the Ni plating, the higher the solder wettability. Therefore, for a film thickness greater than 0.3 μm, although it is not shown in the examples, it is confirmed that there is no problem with solder wettability.
[0161] [Table 8]
[0162]
[0163] Industrial Applicability
[0164] The present invention has the excellent effect of being able to obtain a Ni electroplated film with excellent solder wettability. In addition, while maintaining good solder wettability, it also has the excellent effect of being able to achieve a thin film of the Ni electroplated film. The electroplated film and the electroplated film structure according to the present invention are useful for lead frames, printed wiring boards, rigid substrates, flexible substrates, tape carriers, connectors, power components, leads, pins, etc.
Claims
1. A plating structure, comprising: a substrate composed of Cu or a Cu alloy, a Ni electroplated film formed on the substrate, a Pd electroplated film formed on the Ni electroplated film, and an Au electroplated film formed on the Pd electroplated film, wherein: The Ni electroplating film contains 0.01 wt % or more and 0.61 wt % or less of P, When the P content is 0.01 wt % or more and less than 0.05 wt %, the film thickness of the Ni electroplating film is 0.1 μm or more and 10 μm or less. When the P content is 0.05 wt % or more and less than 0.2 wt %, the film thickness of the Ni electroplating film is 0.06 μm or more and 10 μm or less. When the P content is 0.2 wt % or more and 0.61 wt % or less, the film thickness of the Ni electroplating film is 0.01 μm or more and 10 μm or less.
2. A plating structure, comprising: a substrate composed of Cu or a Cu alloy, a Ni electroplating film formed on the substrate, and a Pd electroplating film formed on the Ni electroplating film, wherein: The Ni electroplating film contains 0.01 wt % or more and 0.61 wt % or less of P, When the content of P is 0.01 wt % or more and less than 0.05 wt %, the thickness of the Ni electroplating film is 0.1 μm or more and 10 μm or less. When the content of P is 0.05 wt % or more and less than 0.2 wt %, the thickness of the Ni electroplated film is 0.06 μm or more and 10 μm or less. When the content of P is 0.2 wt % or more and 0.61 wt % or less, the film thickness of the Ni electroplating film is 0.01 μm or more and 10 μm or less.
3. A plated structure, comprising: a substrate composed of Cu or a Cu alloy, a Ni electroplated film formed on the substrate, and an Au electroplated film formed on the Ni electroplated film, wherein: The Ni electroplating film contains 0.01 wt % or more and 0.61 wt % or less of P, When the content of P is 0.01 wt % or more and less than 0.05 wt %, the thickness of the Ni electroplating film is 0.1 μm or more and 10 μm or less. When the content of P is 0.05 wt % or more and less than 0.2 wt %, the thickness of the Ni electroplated film is 0.06 μm or more and 10 μm or less. When the content of P is 0.2 wt % or more and 0.61 wt % or less, the film thickness of the Ni electroplating film is 0.01 μm or more and 10 μm or less.
4. The plated structure according to any one of claims 1 to 3, wherein As a base of the Ni electroplating film, a metal strike plating film containing any one of Au, Ag, Pd, and Cu is formed.
5. The plated structure according to any one of claims 1 to 3, wherein As a base of the Pd plating film and / or the Au plating film, a metal strike plating film containing any one of Au, Ag, and Pd is formed.
6. A lead frame, wherein: The lead frame has the plated structure according to any one of claims 1 to 3.
Citation Information
Patent Citations
Circuit board
JP1999345896A
Printed-wiring board
JP2006179797A
Electronic component and method of manufacturing the same
JP2009228021A
Electrolysis palladium phosphorus alloy plating liquid, plated film, and plated product
JP2012241260A
Printed wiring board
JP2016162770A